Apego, regulación emocional y funcionamiento familiar en adultos con trastornos por consumo de cocaína - Cócola, Facundo (Revista de Psicopatología y Psicología Clínica, 2022)
Attachment, emotion regulation and family functioning in adults with cocaine use disorders Abstract: The main objective of this study was to analyze the scores, associations and predictions between attachment orientations, emotion regulation and family functioning, in people with substance use disorders. For this purpose, a quantitative, cross-sectional, correlational and predictive study was carried out, in which 183 adults participated (143 men and 40 women), who had cocaine use disorders and did not receive treatment. Results indicated that the majority of the group presented high scores for insecure attachment in close relationships in general (both in avoidance and anxiety), lack of emotional acceptance, and low scores for family cohesion and flexibility. In addition, significant associations were found between difficulties in emotion regulation, insecure attachment orientations and family functioning, the latter two predicting the former, and insecure attachment being the factor that contributed most. Keywords: Substance use disorders; attachment; emotion regulation; family functioning; cocaine. Resumen: El objetivo principal de este estudio fue analizar las puntuaciones, asociaciones y predicciones entre orientaciones de apego, regulación emocional y funcionamiento familiar, en personas con trastornos por consumo de sustancias. Para ello, se realizó un estudio cuantitativo, transversal, de alcance correlacional y predictivo, en el cual participaron 183 adultos (143 hombres y 40 mujeres) con trastornos por consumo de cocaína, que no se encontraban en tratamiento. Los resultados indicaron que la mayoría del grupo presentó puntuaciones elevadas de apego inseguro en las relaciones cercanas en general (tanto en evitación como en ansiedad), falta de aceptación emocional, y bajos puntajes en cohesión y flexibilidad familiar. Además, se encontraron asociaciones significativas entre las dificultades en la regulación emocional, las orientaciones inseguras de apego y el funcionamiento familiar, donde estas dos últimas predicen a la primera, siendo el apego inseguro el factor que más aportó. Palabras clave: trastornos por consumo de sustancias; apego; regulación emocional; funcionamiento familiar; cocaína.